A gaucher patient with bilateral total femoral lytic lesions mimicking malignancy: a case report - AKGÜLLE, AHMET HAMDİ; BUĞDAYCI, ONUR; ERBARUT SEVEN, İPEK; KESKİN ÖZTÜRK, BEYZA (My University, 2022)
Bone involvement in Gaucher disease can afect quality of life. Bone lesions of Gaucher disease can be confused with hematological diseases, infections, and malignancy. Our patient with bilateral femur involvement presented to us with a pathological fracture. After the fracture was treated with a long leg splint and healed, we performed a biopsy because of suspicious radiological fndings. The pathology results confrmed Gaucher disease with bone infltration during the time in which conservative follow-up was taking place, eventually leading to the patient’s mobilization again. Bone fndings of Gaucher disease indicate a difcult process requiring follow-up and treatment. It is crucial to scan patients periodically for possible vertebral and extremity symptoms. Vertebral and extremity fractures undoubtedly require experience on the part of the clinician as they can imitate malignant masses.
Keywords: Gaucher disease; Pathological fracture; Difuse osteopenia